2015
DOI: 10.1088/1367-2630/17/6/063001
|View full text |Cite
|
Sign up to set email alerts
|

The physics of badminton

Abstract: The conical shape of a shuttlecock allows it to flip on impact. As a light and extended particle, it flies with a pure drag trajectory. We first study the flip phenomenon and the dynamics of the flight and then discuss the implications on the game. Lastly, a possible classification of different shots is proposed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
49
1
8

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 50 publications
(58 citation statements)
references
References 12 publications
0
49
1
8
Order By: Relevance
“…4, which provides an example of the temporal history of the drag force coefficient. is comparable in magnitude to Cohen [6]; however, it is higher than data reported by other researchers.…”
Section: Drag Coefficientcontrasting
confidence: 48%
See 4 more Smart Citations
“…4, which provides an example of the temporal history of the drag force coefficient. is comparable in magnitude to Cohen [6]; however, it is higher than data reported by other researchers.…”
Section: Drag Coefficientcontrasting
confidence: 48%
“…This influence of rotation on measured C d was also investigated by Kitta et al [4]. In contrast to Cohen et al [6], the study revealed a freely rotating shuttle had a marginally higher C d ~ 0.61, than a statically fixed shuttle C d ~ 0.56. Both studies concluded that rotation had no significant influence on drag [1].…”
Section: Introductionmentioning
confidence: 75%
See 3 more Smart Citations